Hyperthermia increases sensitivity of pulmonary C-fibre afferents in rats - Ruan, Ting (Blackwell Science Inc, 2005)
This study was carried out to investigate whether an increase in tissue temperature alters the excitability of vagal pulmonary C-fibres. Single-unit afferent activities of 88 C-fibres were recorded in anaesthetized and artificially ventilated rats when the intrathoracic temperature (T(it)) was maintained at three different levels by isolated perfusion of the thoracic chamber with saline: control (C: ∼36°C), medium (M: ∼38.5°C) and high (H: ∼41°C), each for 3 min with 30 min recovery. Our results showed: (1) The baseline fibre activity (FA) of pulmonary C-fibres did not change significantly at M, but increased drastically (>5-fold) at H. (2) The C-fibre response to right-atrial injection of capsaicin (0.5 μg kg(−1)) was markedly elevated at H (ΔFA = 5.94 ± 1.65 impulses s(−1) at C and 13.13 ± 2.98 impulses s(−1) at H; P < 0.05), but not at M. Similar increases in the C-fibre responses to other chemical stimulants (e.g. adenosine, etc.) were found at H; all the enhanced responses returned to control in 30 min. (3) The C-fibre response to lung inflation was also significantly potentiated at H. In sharp contrast, there was no detectable change in either the baseline activity or the responses to lung inflation and deflation in 10 rapidly adapting pulmonary receptors and 10 slowly adapting pulmonary receptors at either M or H. (4) The enhanced C-fibre sensitivity was not altered by pretreatment with indomethacin or capsazepine, a selective antagonist of the transient receptor potential vanilloid type 1 (TRPV1) receptor, but was significantly attenuated by ruthenium red that is known to be an effective blocker of all TRPV channels. (5) The response of pulmonary C-fibres to a progressive increase in T(it) in a ramp pattern further showed that baseline FA started to increase when T(it) exceeded 39.2°C. In conclusion, a pronounced increase in the baseline activity and excitability of pulmonary C-fibres is induced by intrathoracic hyperthermia, and this enhanced sensitivity probably involves activation of temperature-sensitive ion channel(s), presumably one or more of the TRPV receptors, expressed on the C-fibre endings.